Services advertising effectiveness: an investigation into means-end chain connectivity and consumer visualisation of services - Leong, Vai Shiem (2009)
The services advertising literature has called for additional studies of the type of tangible cues and advertising appeal that reduce the intangibility of services. This research proposes that the display of service attributes, as tangible cues, that consumers can easily link to personal values in services advertising messages may enable consumers to mentally visualise a service’s benefits, and thus facilitate the evaluation process. The study draws on principles of the means-end chain and Berry and Clark’s (1986) recommendations for tangibilising services during advertising. Together these perspectives lead to the proposition that advertising messages reflecting important personal values enhance perceptions of tangibility (visualisation strategy) and lead to more positive consumer attitudes.